Contemporary Endovascular Outcomes for Critical Limb Ischemia Are Still Failing to Meet Society for Vascular Surgery Objective Performance Goals. (January 2021) - Latz, Christopher A.; Wang, Linda J.; Boitano, Laura; DeCarlo, Charles; Sumpio, Brandon; Schwartz, Samuel; Lee, Cheong J.; Dua, Anahita
Objectives: The Society for Vascular Surgery (SVS) created Objective Performance Goals (OPGs) for critical limb ischemia (CLI) in 2009. It was previously shown that endovascular therapy for CLI was not meeting these benchmarks. The OPG for all peripheral interventions is <8% for major adverse cardiac events (MACE), <8% for major adverse limb events (MALE), and <3% for major amputation. The goal of this study is to evaluate if outcomes have improved for CLI in recent years, specifically 2015-2018. Methods: The Targeted Vascular Module from the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) was queried to identify patients who underwent endovascular intervention for critical limb ischemia from 2011-2018. Cohorts were divided into 2011-2014 and 2015-2018. Primary 30-day outcomes were MACE, MALE, and major amputation. Univariate analyses were performed using the Fisher's exact test and the Wilcoxon rank-sum test. Multivariate analysis comparing groups was performed using inverse probability weights and trend over time analysis was performed using logistic regression with year of intervention as a continuous variable. Results: From 2011 to 2018, 7, 168 patients underwent an endovascular intervention for CLI. 28% were classified as "OPG high anatomic risk, " and 17% were classified as "OPG high clinical risk." The 2015-2018 cohort vs. the 2011-14 cohort experienced MACE in 3.3% vs. 2.7% (p = .23), MALE in 9.1% vs. 8.9% (p = 0.83), and amputation in 4.0% vs. 4.2% (p = 0.71). When only high anatomic risk patients were considered (n = 1988), MACE was experienced in 2.4% vs. 2.2% (p = 0.87), MALE by 9.5% vs. 10.6% (p = 0.47) and amputation by 5.1% vs. 6.0% (p = 0.40). When only high clinical risk patients were considered (n = 1224), MACE was experienced in 5.2% vs. 3.9% (p = 0.33), MALE by 8.0% vs. 7.4% (p = 0.74) and amputation by 3.9% vs. 3.7% (p = 0.88). Comparing 2015-2018 to the reference 2011-2014, MALE adjusted odds ratio (AOR) = 0.99, 95% CI [0.83-1.18], MACE AOR = 1.19 95% CI [0.88-1.60], and major amputation AOR = 0.91 95% CI [0.70-1.17]. There were no decreases in the trend over time for MALE (AOR per year 0.97, CI [.94-1.02], major amputation (AOR per year: 0.97, CI [0.91-1.03], nor for MACE (AOR per year: 1.05, CI [.98-1.13]). Conclusion: Outcomes following endovascular interventions for CLI continue to underperform when compared to OPG benchmarks for MALE and amputations. There is no decrease over time for these target outcomes. Target MACE events remain acceptable despite the increasing clinical complexity of patients being treated.